2013
DOI: 10.1002/pd.4272
|View full text |Cite
|
Sign up to set email alerts
|

Obstetricians and gynecologists' practice and opinions of expanded carrier testing and noninvasive prenatal testing

Abstract: Rapid incorporation of new genetic technologies may be limited by the availability of genetic counseling, concerns regarding inclusion of clinically mild disorders, results of unknown significance, and costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
102
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(112 citation statements)
references
References 33 publications
8
102
0
2
Order By: Relevance
“…Additional studies cite similar results to support the findings that anxiety, guilt, and stigma do not carry the weight presupposed by some medical professionals 38, 39, 40, 41. It is plausible that physicians and genetic counselors are actually projecting their own anxiety about the time investment and energy required to convey more information onto their patients.…”
Section: Anxiety and Stigmatizationmentioning
confidence: 64%
“…Additional studies cite similar results to support the findings that anxiety, guilt, and stigma do not carry the weight presupposed by some medical professionals 38, 39, 40, 41. It is plausible that physicians and genetic counselors are actually projecting their own anxiety about the time investment and energy required to convey more information onto their patients.…”
Section: Anxiety and Stigmatizationmentioning
confidence: 64%
“…These same issues have been reiterated in other empirical and non-empirical articles (Borry et al 2011;Cho et al 2013;Benn et al 2013;Edwards et al 2015). For many reasons, adequate information is crucial in preconception ECS.…”
Section: Discussionmentioning
confidence: 91%
“…Prenatal screening provides an option for women to abort an affected fetus, while in neonatal screening, the child is already born (Health Council of the Netherlands 2007). In a study surveying gynecologists and obstetricians Fellows of the American College of Obstetricians and Gynecologists, two thirds of respondents indicated that the best time to use expanded carrier screening should be preconceptionally when a couple is planning a pregnancy (Benn et al 2013). This was reiterated by respondents in our study who held the opinion that preconception ECS may reduce abortion incidence.…”
Section: Discussionmentioning
confidence: 99%
“…С помощью секвенирования ново-го поколения (NGS) и специальных компьютер-ных программ даже в минимальном количестве ДНК плода, составляющем 5-10 % по отношению к общему количеству ДНК в крови беременной женщины, удается с высокой вероятностью (97-99 %) определить наличие у плода частых хромосомных болезней, включая синдром Дауна, другие трисомии, нарушения числа половых хро-мосом, многие микроделеционные синдромы и даже ряд генных заболеваний [28][29][30].…”
Section: неинвазивная пренатальная диагностикаunclassified
“…Учитывая высокую эффективность метода, 79 % американских врачей считают, что неин-вазивное пренатальное тестирование по крови матери (НИПт) уже может быть использовано для скрининга синдрома Дауна, а 46 % амери-канских врачей предлагают заменить всю ПД на НИПД [28].…”
Section: неинвазивная пренатальная диагностикаunclassified